One-stage laparoscopy combined with resectoscope in the treatment of huge bladder diverticulum, multiple stones in diverticulum, multiple stones in bladder and benign prostatic hyperplasia: A case report - Zhengqiang, Wan; Yinglei, Wang; Cheng, Li; Dongbing, Zheng (Frontiers in Medicine, 2022)
ABSTRACT Background: Bladder diverticulum is due to the abnormal arrangement of congenital bladder wall muscle fibers, weak limitations, combined with lower urinary tract obstruction, increased intravesical pressure, and protruding between the self-separated detrusor muscle bundles of the bladder wall. Giant bladder diverticulum refers to 10*8cm or diverticulum over 150ml in volume. Case Summary: An 80-year-old male patient was admitted to our hospital on August 14, 2020, the preoperative diagnosis was: bladder diverticulum, bladder diverticulum calculi, multiple bladder stones and prostatic hyperplasia. On August 18, 2020, one-stage laparoscopic bladder diverticulectomy + diverticulum neck incision for stone removal + cystopuncture fistula + transurethral bladder stone removal +transurethral resection of the prostate (TURP) under general anesthesia. First, the bladder diverticulum was separated under laparoscopy, the diverticulum was incised, the diverticulum calculi were taken out, and then the diverticulum was completely removed, and the neck of the diverticulum was extended by 1.5cm, and the large calculus of about 2.7*3.6cm was completely removed, and then cystostomy + transurethral Bladder stone removal + TURP. There was no bleeding from the bladder suture during the operation. 200 mL of urine was drained from the extraperitoneal drainage tube, and 20 mL of urine was drained from the abdominal drainage tube During the operation, the urination is smooth, and the general condition can be discharged. The patient's general condition is good after follow-up. Conclusion: One-stage laparoscopic treatment of bladder diverticulectomy + diverticulum neck incision for stone extraction + cystopuncture fistula + transurethral bladder stone extraction + TURP surgery. There is no report at home and abroad, which can provide diagnosis and treatment ideas and surgical methods for urological colleagues to deal with such diseases.